Health status and public health needs in a Togolese child health care centre modelled after the Dutch system - Paula van Dommelen; Cécile Schat-Savy; Arjan Huizing; Symone Detmar; Leonhard A. Bakker; Paul H. Verkerk (Annals of Human Biology)
Background The charity foundation Association Soutien Enfants Togo started a child health care (CHC) centre in Togo that was modelled after the Dutch high-quality CHC system to improve child health.Aim To describe health care data of children who visited the centre.Subjects and methods Data were routinely collected between October 2010-July 2017. Outcomes were completed vaccinations, growth, development, lifestyle, physical examination, and laboratory testing results.Results In total, 8,809 children aged 0–24 years were available. Half (47.5%) of children aged 0–4 years did not receive all eligible free vaccinations from the government. The proportions of stunted children (all) or with a developmental delay (0–4 years) were 10.1% and 9.5%, respectively. In total, 40–50% of all children did not wash their hands with soap after toilet or before eating, or did not use clean drinking water. Furthermore, 5.1–6.6% had insufficient vision, high eye pressure or hearing loss. Sickle cell disease was detected in 5.3%.Conclusion A large group of children in need of prevention and early treatment were detected, informed and treated by the centre. Further research is needed to confirm if this strategy can improve children’s health in Sub-Saharan Africa. Our data are available for further research.